QoG Basic Dataset - Dahlberg, Stefan; Sundström, Aksel; Holmberg, Sören; Rothstein, Bo; Alvarado Pachon, Natalia; Dalli, Cem Mert (University of Gothenburg, 2013)
The QoG Institute is an independent research institute within the Department of Political Science at the University of Gothenburg. Overall 30 researchers conduct and promote research on the causes, consequences and nature of Good Governance and the Quality of Government - that is, trustworthy, reliable, impartial, uncorrupted and competent government institutions.

The main objective of our research is to address the theoretical and empirical problem of how political institutions of high quality can be created and maintained. A second objective is to study the effects of Quality of Government on a number of policy areas, such as health, the environment, social policy, and poverty.

QoG Basic Dataset, which consists of approximately the 300 most used variables from QoG Standard Dataset, is a selection of variables that cover the most important concepts related to Quality of Government.

In the QoG Basic CS dataset, data from and around 2018 is included. Data from 2018 is prioritized, however, if no data is available for a country for 2018, data for 2019 is included. If no data exists for 2019, data for 2017 is included, and so on up to a maximum of +/- 3 years.

In the QoG Basic TS dataset, data from 1946 to 2021 is included and the unit of analysis is country-year (e.g., Sweden-1946, Sweden-1947, etc.).

The primary aim of QoG is to conduct and promote research on corruption. One aim of the QoG Institute is to make publicly available cross-national comparative data on QoG and its correlates.

QoG-institutet är ett oberoende forskningsinstitut som tillhör Statsvetenskapliga institutionen vid Göteborgs universitet. Sammanlagt är det ungefär 30 forskare som bedriver internationell forskning om orsaker till och konsekvenserna av korruption och samhällsstyrningens kvalitet.

Forskningen fokuserar på det teoretiska och empiriska problemet hur politiska institutioner av hög kvalitet kan skapas och upprätthållas, samt studerar effekterna av samhällsstyrningens kvalitet på ett antal olika politikområden, som exempelvis hälsa, miljö, socialpolitik och fattigdom.

QoG Basic Dataset, som består av ungefär av de 300 mest använda variablerna från QoG Standard Dataset, är ett urval antal variabler som täcker de viktigaste begreppen relaterade till Quality of Government.

I QoG Basic CS datasetet ingår data från omkring 2018. Data från 2018 är prioriterat, men där inga uppgifter finns tillgängliga för 2018 för ett specifikt land så ingår data för 2019. Om inga uppgifter finns tillgängliga för 2019 så ingår data för 2017 och så vidare upp till max +/- 3 år.
I QoG Basic TS datasetet ingår data från 1946 till 2021 och analysenheten är land-år (t.ex. Sverige-1946, Sverige-1947, etc.).

QoG:s huvudsakliga syfte är att bedriva och främja forskning om korruption. Ytterligare ett syfte med institutet är att offentliggöra nationellt gränsöverskridande och jämförbara data.
QoG Basic Dataset
Keywords: STATE CONTROL; STATLIG STYRNING; POLITICAL INSTITUTIONS; POLITISKA INSTITUTIONER; CORRUPTION; KORRUPTION; DATA; DATA; BUREAUCRACY; BYRÅKRATI; PUBLIC ADMINISTRATION; OFFENTLIG FÖRVALTNING; GOVERNMENT ORGANIZATIONS; STATLIGA ORGANISATIONER; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap